The emerging Indian Ocean landscape: security challenges and evolving architecture of cooperation – an Australian perspective - Rumley, Dennis (Routledge, 2015)
© 2015 Indian Ocean Research Group. This paper analyses two interrelated issues. The first is a description and discussion of Australian identity dilemmas and contested regionalisms as a backdrop to an understanding of Australia's degree of engagement with regional security regimes. Throughout its post-colonial history Australia has been characterised according to three main geopolitical orientations – continental, geopolitical role and maritime. It is argued that Australia only came to fully realise its maritime orientation in policy terms towards the end of the Cold War period. The second issue in this paper evaluates arguments in favour of the need for an overall Indian Ocean Maritime Security Regime (IOMSR) and it is suggested that an inclusive model, built around energy security stakeholders, is much preferred from the viewpoint of long-term regional stability. This paper describes overall Indian Ocean (IO) regional security concerns and arrangements and then focuses on the nature of IO maritime security and insecurity and the initiatives currently in place to deal with such issues. Five options for the creation of a new IOMSR are described and evaluated and Australia's place within each of these is discussed.